Benefits and risks of weight-loss treatment for older, obese women - Rossen LM (Dove Medical Press, 2013)
Lauren M Rossen,1,2 Vanessa A Milsom,1,3 Kathryn R Middleton,1,4 Michael J Daniels,5,6 Michael G Perri1,71Department of Clinical and Health Psychology, University of Florida, Gainesville, FL, USA; 2National Center for Health Statistics, Centers for Disease Control and Prevention, Hyattsville, MD, USA; 3Department of Psychiatry, Yale University School of Medicine, New Haven, CT, USA; 4Weight Control and Diabetes Research Center, Department of Psychiatry and Human Behavior, Warren Alpert Medical School of Brown University and The Miriam Hospital, Providence, RI, USA; 5Department of Statistics, University of Florida, Gainesville, FL, USA; 6Division of Statistics and Scientific Computation, University of Texas at Austin, Austin, TX, USA; 7College of Public Health and Health Professions, University of Florida, Gainesville, FL, USABackground: A key issue in the treatment of obesity in older adults is whether the health benefits of weight loss outweigh the potential risks with respect to musculoskeletal injury.Objective: To compare change in weight, improvements in metabolic risk factors, and reported musculoskeletal adverse events in middle-aged (50–59 years) and older (65–74 years), obese women.Materials and methods: Participants completed an initial 6-month lifestyle intervention for weight loss, comprised of weekly group sessions, followed by 12 months of extended care with biweekly contacts. Weight and fasting blood samples were assessed at baseline, month 6, and month 18; data regarding adverse events were collected throughout the duration of the study.Results: Both middle-aged (n = 162) and older (n = 56) women achieved significant weight reductions from baseline to month 6 (10.1 ± 0.68 kg and 9.3 ± 0.76 kg, respectively) and maintained a large proportion of their losses at month 18 (7.6 ± 0.87 kg and 7.6 ± 1.3 kg, respectively); there were no significant differences between the two groups with respect to weight change. Older women further experienced significant reductions in systolic blood pressure, HbA1c, and C-reactive protein from baseline to month 6 and maintained these improvements at month 18. Despite potential safety concerns, we found that older women were no more likely to experience musculoskeletal adverse events during the intervention as compared with their middle-aged counterparts.Conclusion: These results suggest that older, obese women can experience significant health benefits from lifestyle treatment for obesity, including weight loss and improvements in disease risk factors. Further investigation of the impact of weight loss on additional health-related parameters and risks (eg, body composition, muscular strength, physical functioning, and injuries) in older adults is needed.Keywords: lifestyle intervention, adverse events, metabolic risk factors